Complex regional pain syndrome of the knee after conventional radiofrequency ablation of the genicular nerves treated successfully with dorsal root ganglion stimulation: A case report. Issue 5 (18th May 2022) - Belba, Amy; Vanneste, Thibaut; Jerjir, Ali; Smeets, Kristof; Van Buyten, Jean‐Pierre; Bellemans, Johan; Van Zundert, Jan
Abstract: Background: Radiofrequency (RF) treatment of the genicular nerves offers pain relief in patients suffering from chronic knee pain including persistent post‐surgical knee pain (PPSP). We present the first case report of the development of complex regional pain syndrome (CRPS) in a chronic knee pain patient after an RF ablation of the genicular nerves that was successfully treated with dorsal root ganglion (DRG) stimulation. Case Presentation: The patient developed increased pain, sympathetic and dysmorphic changes of the index knee 10 weeks after RF treatment for PPSP. Diagnosis of CRPS type II was made using positive clinical findings and the Budapest diagnostic tool. Laboratory workup and PET‐CT were negative. The patient was refractory to usual care and she was treated successfully with dorsal ganglion root stimulation. Conclusions: Complex regional pain syndrome is a possible complication of RF ablation of the genicular nerves in patients with chronic knee pain, and DRG stimulation may be a treatment option. Physicians should be aware of this complication, especially when patients have a medical history of CRPS.